Mobile Complex for the Production of Expanded Clay for the Northern Roads - M. N. Kokoev; V. T. Fedorov (Вестник Дагестанского государственного технического университета: Технические науки, 2022)
Objective. International practices demonstrate advantages of expanded clay in road construction in difficult climatic and geotechnical conditions. The clay is present in abundance in Siberia and in the Far North which is suitable for the production of expanded clay gravel. At the same time there is a strong deficit of the road construction materials in these regions. The aim of the study is to develop a new approach for providing claydite for the construction of northern roads.Method. The modernization of the equipment means that each unit included in the complex can be transported on existing trucks, and then mounted in a line for the production of expanded clay in the field.Result. A mobile complex for the production of expanded clay gravel, serial and modernized equipment for the production of expanded clay has been developed.Conclusion. Large units - drying drums and rotary kilns for drying and firing pellets should be divided into prefabricated sections, for example, with a diameter of 2 m and a length of 5-7 m. For the electric drive of the units, a diesel generator of sufficient power must be included in the equipment set. The productivity of one complex is from 15 thousand cubic meters of expanded clay per year and above.